Potential and Challenges of Biofuels from Keruing (Dipterocarpus spp.) to Support Sustainable Fuel Transition in the Transportation Sector - Nurin Alwaaritsy; Arista Romadan (Jurnal Ilmu Pertanian Indonesia, 2025)
Mobility is an integral part of daily life; however, the transportation sector significantly contributes to greenhouse gas emissions, which trigger global warming. In the context of climate change, a global issue, the Paris Agreement and the Nationally Determined Contribution (NDC) policies of each country encourage the development of environmentally friendly, renewable energy. Keruing (Dipterocarpus spp.), a tree found only in tropical forests, has the potential to be a source of biofuel from its non-timber products such as oil and resin. This study aims to analyze the challenges of developing biofuel from keruing for the transportation sector in Indonesia, using a mixed method enhanced by machine learning for data analysis. The results show that keruing oil has potential as a biofuel, but the main challenges lie in infrastructure, knowledge limitations, and processing techniques. Many keruing trees with oily wood are not industrially processed for their oil due to a lack of knowledge and a focus on wood utilization. The conclusion is that the potential for developing environmentally friendly renewable energy in Indonesia is significant, but improving the quality of human resources and capital is necessary to advance the science and technology. Keywords: biofuel, Dipterocarpus spp., energy transition, SDGs, transportation